2021
DOI: 10.3390/biom11121896
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone for Inner Ear Therapy: Biocompatibility and Bio-Efficacy of Different Dexamethasone Formulations In Vitro

Abstract: Dexamethasone is widely used in preclinical studies and clinical trials to treat inner ear disorders. The results of those studies vary widely, maybe due to the different dexamethasone formulations used. Laboratory (lab) and medical grade (med) dexamethasone (DEX, C22H29FO5) and dexamethasone dihydrogen phosphate-disodium (DPS, C22H28FNa2O8P) were investigated for biocompatibility and bio-efficacy in vitro. The biocompatibility of each dexamethasone formulation in concentrations from 0.03 to 10,000 µM was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…However, although many studies highlight the therapeutic effect of DEX, factors such as the polarity of pro-drugs, the concentration to be applied or the delivery route affect its biological effects. In in vitro studies, the same DEX used as in this study was shown to be biocompatible up to 2000 µM (0.0784 mg/mL) [23]. In addition, this DEX was used for delivery through hydrophobic materials such as silicone in previous studies [24,25].…”
Section: Dexamethasonementioning
confidence: 75%
“…However, although many studies highlight the therapeutic effect of DEX, factors such as the polarity of pro-drugs, the concentration to be applied or the delivery route affect its biological effects. In in vitro studies, the same DEX used as in this study was shown to be biocompatible up to 2000 µM (0.0784 mg/mL) [23]. In addition, this DEX was used for delivery through hydrophobic materials such as silicone in previous studies [24,25].…”
Section: Dexamethasonementioning
confidence: 75%
“…Dexamethasone is a glucocorticoid with anti-inflammatory and antioxidant properties widely used in hearing loss treatment but also in basic research [ 53 , 54 ]. However, it is known that systemic administration can cause numerous side effects due to steroids accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is known that systemic administration can cause numerous side effects due to steroids accumulation. For this reason, local administration, for example, through the tympanic membrane, is preferred for the inner ear [ 54 , 55 ]. In the recent literature, there is an increasing number of studies in which dexamethasone is spread through the electrode of cochlear implants [ 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…To overcome these drawbacks, the local release of low amounts of dexamethasone over prolonged periods of time has been proposed ( Astolfi et al, 2016 ; Bas et al, 2016 ; Douchement et al, 2015 ; Qnouch et al, 2021 ). Several beneficial effects of such a glucocorticoid treatment can be expected: (i) The importance of inflammation caused by implant placement can be reduced, (ii) fibrosis be limited, and (iii) the life-time expectancy of remaining hair cells be increased ( Jia et al, 2016 ; Liu et al, 2015 ; Gao et al, 2021 ; Toulemonde et al, 2021 ). One possible strategy is to incorporate dexamethasone into the silicone matrices separating the metal electrodes in the cochlear implants ( Farahmand Ghavi et al, 2010 ; Krenzlin et al, 2012 ; Farhadi et al, 2013 ; Liu et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%